Pb Exposure to Hair and Nails in The Workers in Basement Parking Lot of Lippo Plaza Mall Yogyakarta - Maria Roosa Srah Darmanijati; Ari Ramelan; Pranoto; Inayati (Environmental Insight Journal, 2026)
This study was performe in LG basement lippo Plaza Mall Yogyakarta. The aim to provide Pb exposure Pb from transport activity. Analysis of hair and nails is known to provide useful information about environmental and toxic exposures. The research was conducted in May 2021. Nails and hair are good bioindicators to detect contaminants.We studied 30 human hair and nails samples in workers who work inside Basement Park. Hair and finger nail samples were collected from all respondent. Personal characteristics included: age, long work, background and health conditions of the respondent. The fingernail clippings were obtained using a stainless steel nail clipper and hair cut by hair scissors. The sample keep in self-adhesive plastic bag for later analysis by Analytical Methods for Atomic absorption Spectroscopy ( AAS). The values of lead concentrations in nail and hair of the subjects were presented as arithmetic mean (ppm) with standard error (±SE) and tabulated to show concentration profile over each parameter. The One-Sample Kolmogorov-Smirnov Test were used to describe distribution test and and the Mann-Whitney U test was used to corelate the concentrations between lead concnetrations from long perithe two groups. The level of significance was set at Pb 0.05. All calculations were performed using statistical packages SPSS (version 21). Respondents with a working period of less than 4 years detected an average Pb of 3.9671 ppm with a Standard Error (SE) of 1.5, an average of 5-8 years of service period of 4.0312 with an SE of 1.58 and an average working period of more than 9 years. The average Pb content was 13.0805 with an SE of 7.07. From these results, it shows that the longer the employee's working period, the higher the level of Pb in his nails or hair. The results of the regression test showed that there was no effect of work and the results of measuring Pb levels in nails/hair because the sig value was 0.496 > p = 0.05 with R square: 0.017. The average levels of Pb in the nails and hair of workers working around the basement were security 0.849 ppm, engineers 4.87 ppm, cleaning service 7.17 ppm and parking guards 7.74 ppm . It is recommended to continue to rotate employee turnover times with shorter time for parking staff and use masks for cleaning services.